2023
DOI: 10.1186/s40246-023-00452-0
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide allele and haplotype-sharing patterns suggested one unique Hmong–Mein-related lineage and biological adaptation history in Southwest China

Abstract: Background Fine-scale genetic structure of ethnolinguistically diverse Chinese populations can fill the gap in the missing diversity and evolutionary landscape of East Asians, particularly for anthropologically informed Chinese minorities. Hmong–Mien (HM) people were one of the most significant indigenous populations in South China and Southeast Asia, which were suggested to be the descendants of the ancient Yangtze rice farmers based on linguistic and archeological evidence. However, their dee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 80 publications
2
6
0
Order By: Relevance
“…5 D). We interestingly identified that Hmong people from Southeast Asia possessed the largest proportion of O2 lineage, which was consistent with the long-distance population migration and connection inferred from the genome-wide SNP data [ 57 ]. The reconstructed phylogenetic relationship based on the pairwise Fst matrix showed two major branches associated with the stratification of haplogroup composition of Southeast and East Asia (Fig.…”
Section: Resultssupporting
confidence: 81%
“…5 D). We interestingly identified that Hmong people from Southeast Asia possessed the largest proportion of O2 lineage, which was consistent with the long-distance population migration and connection inferred from the genome-wide SNP data [ 57 ]. The reconstructed phylogenetic relationship based on the pairwise Fst matrix showed two major branches associated with the stratification of haplogroup composition of Southeast and East Asia (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Public data from the HGDP [ 74 ] and Oceania genomic resource [ 12 ], AADR (HO dataset and 1240 K dataset) [ 75 ] from David Reich Lab [ 76 ], and our previously reported populations genotyped via Affymetrix Array chip [ 26 , 39 42 ] were included to form the following four merged datasets. The high-density SNP dataset included population data from Miao, Jing, Zhuang, Li, Tujia, and Mongolian, which included 465,941 SNPs [ 40 43 , 77 , 78 ]. High-density global dataset included populations from HGDP and Oceania genomic resources, which included 424,501 SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…The results of Liu et al's analysis of Y-SNPs and Y-STRs both indicated that patients with esophageal cancer (EC) and gastric cardia cancer in the Chaoshan region have a closer genetic affinity with patients from the Taihang Mountains, and the relationship between patients and high-risk populations was even tighter [ 9 ]. He et al revealed the unique natural selection signatures and biological adaptations of Hmong-Mien speakers through SNP-based allele and haplotype sharing and identified genetic loci linked to immune dysfunction, alcohol, and coronary heart disease in Hmong-Mien speakers in Southwest China's Guizhou region [ 10 ]. Combining SNPs and Y-STR analysis with the study of the genetic background of populations specific to certain diseases has revealed the genetic patterns of these groups, emphasizing the importance of considering genetic diversity in disease research.…”
Section: Introductionmentioning
confidence: 99%